2016
DOI: 10.20471/acc.2016.55.s1.16
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Management of a Patient With Central Airway Compression Due to Posterior Mediastinal Mass

Abstract: SUMMARY -Patients with mediastinal masses present unique challenge to anesthesiologists. Patients with anterior mediastinal masses have well documented cases of respiratory or cardiovascular collapse during anesthesia and in postoperative period. Masses in the posterior mediastinum have been traditionally regarded to carry a significantly lower risk of anesthesia related complications but cases of near fatal cardiorespiratory complications have been reported. We describe anesthetic management of a patient with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The literature review revealed a few case reports that have described different approaches to managing BCs located in various mediastinal regions. For instance, Sulen et al [17] employed awake fiberoptic intubation with an endobronchial tube for a cyst in the posterior mediastinum, while Wools et al [18] conducted an emergency tracheostomy for cysts in the superior mediastinum, which presented with a stridor and was later managed with a thoracotomy. Furugen et al [19] addressed a recurrent BC tightly attached to the left atrium through sternotomy and CPB.…”
Section: Figure 6: Postoperative Chest X-ray Pa View Discussionmentioning
confidence: 99%
“…The literature review revealed a few case reports that have described different approaches to managing BCs located in various mediastinal regions. For instance, Sulen et al [17] employed awake fiberoptic intubation with an endobronchial tube for a cyst in the posterior mediastinum, while Wools et al [18] conducted an emergency tracheostomy for cysts in the superior mediastinum, which presented with a stridor and was later managed with a thoracotomy. Furugen et al [19] addressed a recurrent BC tightly attached to the left atrium through sternotomy and CPB.…”
Section: Figure 6: Postoperative Chest X-ray Pa View Discussionmentioning
confidence: 99%